Attracting Future Health Workforces in Geographically Remote Regions: perspectives from current remote health professionals - Leighanne Onnis (ACHSM, 2017)
Objective: The aim of this study was to identify what has previously attracted health professionals to work in geographically remote regions, to identify the incentives that managers are currently using to attract health professionals to remote regions, and to determine whether they are comparable. Design: This article examines the data from two separate, yet complementary, research studies. The first study used qualitative methods to investigate why health professionals choose to work in geographically remote regions through current remote health workforces. The second study investigated whether information communicated through recruitment advertising contained information congruent with the themes that attracted the current remote health professionals through a content analysis of recruitment advertisements. The findings from these two studies are then compared and contrasted and Psychological Contract Theory is used to examine the implications for health service managers. Setting: This study was conducted in northern Australia, a remote tropical setting with geographically challenging working conditions. Results: The findings revealed that recruitment advertisements contained information comparable with the themes that had attracted health professionals to work in remote regions. Most importantly, they highlight opportunities to better align recruitment practices, and provide insight into how unrealistic expectations lead to psychological contract breaches. Conclusions: This study found that while recruitment advertisements are using appropriate content to attract health professionals to remote regions, there is considerable scope for improvement so that attraction translates into improved retention.